ANALISIS OPTIMALISASI MANAJEMEN EKONOMI PONDOK PESANTREN NURUL HUDA KOTA TANGGERANG - Muhammad Najib Murobbi (university Of islam, 2023)
The purpose of this research is to find out how the pentahelix model optimizes the management of Islamic boarding school fertilization business units. In the process of optimizing the Nurul Huda Islamic boarding school applying management knowledge, entrepreneurship training and santripeneur training. This study used a qualitative approach by collecting data through interviews, observation and documentation. The muwajjahah method as a training method for the santripeneuer program is in the form of plant fertilizer at UD Mitra Pesantren Berkah Tani. The results of the study show that optimization can be identified by applying the pentahelix model which consists of academics, business people, government, community and media. Academics consist of teachers, entrepreneurship coaches and parties related to santripenuer. The business actors consist of the UD Mitra Pesantren fertilizer production team. The government consists of the Tangerang City Islamic Boarding School Gathering Forum (FSPP), which is the auspices of the Ministry of Religion. The community consists of companies and factories that act as accelerators in the process of developing santripenuer, and the media is a marketing strategy in the process of selling fertilizer. As a form of sustainable optimization, the Nurul Huda Islamic boarding school must be able to balance students with provisions in the form of a curriculum as a reference for learning and fostering students. In several Islamic boarding schools in Indonesia, not many Islamic boarding schools have implemented this pentahelix model as an optimization. This research is expected to provide broader knowledge about management optimization. As the researcher provides a concept and idea of the Nurul Huda Islamic boarding school by applying the pentahelix model.